Plan de negocios para la creación de una empresa comercializadora de frutas en el cantón Quinsaloma, provincia de Los Ríos, año 2015. - Mantilla Perugachi, Ivonne Elizabeth (2016)
This research work allows a business plan for the creation of a trading company of fruit in the Quinsaloma Canton province of Los Ríos, 2015, because there is no suitable place for buy fruits as existing merchants retailed food products on public streets and the municipal market in unpleasant conditions for the lack of cleanliness and hygiene causing that people do not make purchases obtaining dissatisfaction with what was raised to identify the supply and demand of the inhabitants of the canton of Quinsaloma through economically active population indicates 9,053 inhabitants by 2015, with a proportional sample of 369 people surveyed, resulting in that 100% of respondents consume fruits also considered that the most preferred qualities when making purchases of fruits by respondents it is the freshness with 24%, hygiene and cleanliness 22%, prices 18%, quality 16% and attention with 15%, demonstrating that the inhabitants of the canton of Quinsaloma if they would like with 99% one marketer of fresh fruits with excellent products that provide the qualities of their choice, obtaining for the first year of projected unmet demand for 65,876 people who are satisfied with the fruits sold in the canton of Quinsaloma, also the technical study that determined the micro was developed and macro location of the project, availability of resources, project engineering that establishes the processes necessary for the creation of effective and efficient marketing of fruit, with financial economic study indicated the total investment is $ 25,245.90 for creating the marketing of fruit, getting through profitability indicators net present value to $ 36,046.88, the internal rate of return 54% and the benefit cost $ 1.32 which makes feasible the development of the project, why the proposal identifies the mix of marketing strategies to position the company in the minds of consumers and to attract customers. Keywords: business plan, marketing, research, supply and marketing of fruit demand.